Bulgaria : Teaching Workforce Developments and Recommendations - World Bank (World Bank, Washington, DC, 2022)
Like many European countries, Bulgaria’s workforce is facing dynamic developments influenced by negative demographic trends, seasonal and long-term migration of the population both in the country and abroad, imbalanced economic development of the Bulgarian regions, learning opportunities in the country and abroad, and diverse economic developments between the sectors of the economy. This context is strongly influencing the education sector with an aging workforce and shrinking student population.